2020
DOI: 10.33448/rsd-v9i7.3953
|View full text |Cite
|
Sign up to set email alerts
|

Telemonitoramento em enfermagem: contribuições para autonomia de pessoas com diabetes mellitus tipo 2

Abstract: Telemonitoring is a secure technology that consists of telephone calls with the objective of stimulating, accompanying and supporting people with health needs, remote monitoring and continuous learning. Objectives: to analyze participants' knowledge and expectations regarding diabetes and their health; discuss the repercussions of telemonitoring for the self-care of this specific group. Method: This is a qualitative research, with a participatory approach, developed in 2018, at the outpatient clinic of the Pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 15 publications
0
2
0
5
Order By: Relevance
“…In the context of nursing care, they can enhance and qualify care actions, since they help in the process of learning and self-knowledge of the individual regarding their health condition (25) . In the studies identified in this review, the TEs used were: printed technologies (15)(16) ; interactive technologies and mobile applications (18)(19)(20)22) ; telemonitoring (21) ; simulation (17) ; and audiovisual production (14) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of nursing care, they can enhance and qualify care actions, since they help in the process of learning and self-knowledge of the individual regarding their health condition (25) . In the studies identified in this review, the TEs used were: printed technologies (15)(16) ; interactive technologies and mobile applications (18)(19)(20)22) ; telemonitoring (21) ; simulation (17) ; and audiovisual production (14) .…”
Section: Discussionmentioning
confidence: 99%
“…Duarte (21) Map-speaker (MF), telemonitoring and interview / Telemonitoring Effective in stimulating and enhancing health care VI Silva (22) Unrealized /Interactive digital app It is an interactive support for health education actions and an incentive for preventive self-care. VII Chart 2 (concluded)…”
Section: IImentioning
confidence: 99%
“…Duarte (21) 2020/Português/ Brasil Pesquisa-ação com abordagem qualitativa 14 participantes com diabetes mellitus tipo 2…”
Section: Referência Intervenção / Tecnologia Educativa Desenvolvida P...unclassified
“…Duarte (21) Mapa-falante (MF), telemonitoramento e entrevista / Telemonitoramento Eficaz ao estímulo e potencialização dos cuidados de saúde VI Silva (22) Não realizada / Aplicativo digital interativo Constitui um suporte interativo para ações de educação em saúde e incentivo ao autocuidado preventivo. VII qualificar as ações de cuidado, uma vez que auxiliam no processo de aprendizado e autoconhecimento do indivíduo quanto à sua condição de saúde (25) .…”
Section: IIunclassified
See 1 more Smart Citation